Quality of life of patients with inflammatory bowel disease - Vivan,Thais Karla (2017)
ABSTRACT Rationale: Crohn's disease and non-specific ulcerative colitis are part of inflammatory bowel diseases. They have a chronic evolution, leading to important repercussions on patients’ quality of life. Measuring this subjective parameter requires an evaluation tool in clinical trials and health programs. The “Inflammatory Bowel Disease Questionnaire” is an American instrument of McMaster University, which had its reproducibility and validity determined in studies in other countries as a measure of the quality of life in IBD. Objective: To evaluate the quality of life of patients with inflammatory bowel disease through the Inflammatory Bowel Disease Questionnaire, and to correlate the results with sociodemographic data of the patients. Methods: This is a prospective cross-sectional study carried out with 58 patients; the patients’ follow-up was conducted at the outpatient clinic of Coloproctology. Results: Among the 58 patients evaluated, 70.1% had DC, 62.1% were women, the mean age was 46.08 years, 96.6% were non-smokers, and 24.1% were submitted to surgery for the underlying disease. 43% were in a combination therapy scheme, 44% in monotherapy, and 12% were not using medication. Significant change in quality of life was observed in patients taking prednisone. Conclusion: The patients with better quality of life are those who were taking prednisone. There was no other correlation with significance in the patients’ quality of life.